Approved cannabinoids for medical purposes: comparative systematic review and meta-analysis for sleep and appetite - Spanagel, Rainer; Bilbao, Ainhoa (Neuropharmacology, 2021)
Background - Cannabinoids are used for numerous disease indications. However, cannabinoids can also produce adverse effects; for example, they can disturb physiological functions such as sleep and appetite. The medical use of cannabinoids refers to a wide variety of preparations and products. Approved cannabinoid products include dronabinol ((−)-trans-Δ9-tetrahydrocannabinol (THC), nabilone (a THC analogue), and cannabidiol (CBD) that differ in their pharmacology and may thus have different adverse effects on sleep and appetite. - Objectives - Here we ask if (i) cannabinoids decrease sleep and appetite in somatic patients or patients that suffer from mental illness and if (ii) there is a difference between THC products (nabilone, dronabinol), vs. CBD in disturbing these physiological functions. - Methods - In order to answer these two questions, we performed a comparative systematic review (SR) for nabilone, dronabinol, and CBD. For the comparative SR we searched PubMed, Medline, Embase, and PsycINFO for randomized controlled trials (RCTs) and extracted information for adverse side effects or outcomes reporting a negative impact on sleep and appetite. RCT evidence was calculated as odds ratios (ORs) via fixed effects meta-analyses. Evidence quality was assessed by the Cochrane Risk of Bias and GRADE tools. This study is registered at PROSPERO (CRD42021229932). - Findings - A total of 17 RCTs (n = 1479) and 15 RCTs (n = 1974) were included for sleep and appetite, respectively. Pharmaceutical THC (nabilone, dronabinol) does not affect sleep or appetite. In contrast, there is moderate evidence that CBD decreases appetite (OR = 2.46 [1.74:4.01] but has also no effect on sleep. - Interpretations - Our comparative systematic study shows that approved cannabinoids can decrease appetite as a negative side effect - an effect that seems to be driven by CBD. Approved cannabinoid products do not negatively affect sleep in somatic and psychiatric patients. This article is part of the special Issue on “Cannabinoids”.
Gesehen am 31.01.2023